Intersectionality and Female Solo Travel: Rethinking Motivations Amidst Conservative Gender Norms - Rostami, Afsaneh; Daniels, Gary; Trupp, Alexander; Chaichi, Kamelia (Journal of Ethnic and Cultural Studies, 2026)
Female solo travel has emerged as a significant sociocultural phenomenon, frequently associated with personal growth, independence, and empowerment. In contexts where gender norms and mobility rights are severely constrained, however, travel solo takes on additional meanings and constraints. In Iran, where Islamic regulations, entrenched patriarchal traditions, and political structures rigorously shape women’s mobility, the motivations for solo travel are deeply interwoven with social identity and lived experience. Drawing on 52 interviews with 25 Iranian women conducted in Malaysia, supplemented by photo-elicitation and serial interviews, this research employs a constructivist grounded theory approach to uncover the fluid, context-specific nature of solo travel motivations. The findings distinguish between solo travel by default, driven by external circumstances such as work, education, or the absence of a companion, and solo travel by choice, motivated by aspirations for freedom, psychological well-being, and self-discovery. Participants often treated even brief periods of unaccompanied transit as meaningful, given expectations of accompaniment. By situating female solo travel within the socio-cultural and political landscapes of Iran, this research contributes to a more intersectional and context-sensitive understanding of women’s mobility across Asia, highlighting how meanings attached to solo travel vary across social position and life stage.